The die is cast: Youth, mobilizations and politics in Latin America in the post-pandemic scenario (Polis (Santiago), 2023)
The dossier aims to explore and understand, through empirical research, which specific elements of mobilization allow understanding the ways of life of youths, as well as the singularities of political cycles and Latin American forms of mobilization from a generational perspective. As a result, we gathered four articles with case studies of youth mobilizations in Latin America, specifically two from Argentina, one from Brazil and one from Chile. We highlight in the texts the importance of feminist struggles that politically socialized young people who started to fight for other demands, such as the environmental issue, without leaving aside the inequalities related to the world of work. The strategies of the movements presented also reveal the importance of interaction with state institutions.
Keywords: Youth; Social Movements; Generation